PENERAPAN PEMBELAJARAN DISCOVERY LEARNING DENGAN ALAT PERAGA TIMBANGAN UNTUK MENINGKATKAN KEMAMPUAN PENYELESAIAN MATEMATIKA - Widyawati, Lilis; Kartika, Era Dewi; Widiantoro, Endah (Universitas Insan Budi Utomo, 2024)
The aim of this research is to describe the application of the discovery learning learning model with scales to improve PLSV Completion Ability. There has not been much research on discovery learning using scales as a tool. The research method used is qualitative descriptive. The research subjects were 22 students in class VII A of SMPN 3 Tirtoyudo Satu Roof. Data collection techniques are carried out by observing during the learning process, student answers and student learning outcomes. The research results show that students' ability to complete PLSV increases, student learning outcomes also increase, and the learning process is more meaningful. Students whose ability to solve PLSV questions had increased and developed reached 14.8%, namely 4 students, students who developed according to expectations reached 37.1%, namely 10 students, students who were starting to develop reached 29.6%, namely 8 students. students and 5 students have not developed their ability to solve PLSV questions.